(untitled) (Eureka Journal of Humanities and Social Research, 2026)
The article analyzes the dialectical relationship between social consciousness, political identity and civilized self in the context of the formation of the new world order. The study used Hegel’s dialectic, Gramshi’s theory of hegemony, Castells’ concept of the network society, and Bourdie’s social field theory as methodological frameworks. It is shown that today’s global changes reshape social consciousness not only at the intersection of traditional ideological factors, but also at the intersection of civilizational awareness, national identity, and global information flows. Political identity is a phenomenon that is not rigid and permanent, but arises from a constant dialectical movement of social practice, cultural memory, and discourses of power. The civilized self, while being a product of historical sedimentations, is also the object of modern normative struggles. On the example of Uzbekistan, the features of the reconstruction of post-Soviet identity are revealed. The result suggests that rather than Huntington’s "clash of civilizations" model, current processes have the character of "dialogue and competition of civilizations" and have a complex dialectic character rather than a distinctly biased conflict.